How Initial Word Reading and Language Skills Affect Reading Comprehension Outcomes for Students With Reading Difficulties. (January 2019) - Vaughn, Sharon; Roberts, Greg; Capin, Philip; Miciak, Jeremy; Cho, Eunsoo; Fletcher, Jack M.
This study examined how differences in listening comprehension and word reading at the beginning of the school year influence changes in reading comprehension for English learners (ELs) with significant reading difficulties compared to non-ELs with significant reading difficulties. The study investigated heterogeneity in response to instruction among 400 struggling readers in fourth grade ( n = 183 for non-EL; n = 217 for EL) who received an intensive reading intervention. At pretest, word reading, listening comprehension, and reading comprehension were measured, and at posttest, reading comprehension was measured again. Results from moderated multiple regression analyses showed a significant three-way interaction such that reading comprehension at posttest was higher for ELs than non-ELs with similar levels of low word reading but relatively higher levels of listening comprehension. However, non-ELs outperformed ELs with similar levels of relatively high word reading and average to high listening comprehension. The findings suggest that pre-intervention skill profiles may need to be interpreted differently for ELs and non-ELs with significant reading difficulties in relation to language and literacy outcomes.